2019
DOI: 10.1155/2019/8693516
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating Chemerin in Relation to Chronic Microvascular Complications in Patients with Type 2 Diabetes

Abstract: Objective. Type 2 diabetes (T2DM) is a global epidemic and increases mortality due to its vascular complications. Chemerin has been found to exert a major role in glucose and lipid metabolism. The aim of this study was to explore the correlation between plasma chemerin levels and microangiopathy in patients with T2DM. Methods. A total of 598 T2DM patients were classified into two groups: with and without microvascular complications. Anthropometric parameters and blood pressure were taken. The amounts of glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Serum concentrations of chemerin is increased in metabolic syndromes and corresponds well with components of metabolic syndrome phenotypes: obesity, adverse lipid profile, increased blood pressure, diabetes and prediabetes, and hepatic steatosis [1,[7][8][9][10]. It contributes to several diabetes complications: diabetic nephropathy, retinopathy, or coronary artery disease (CAD) [2,[11][12][13][14][15]. It is elevated in patients with dilated cardiomyopathy [16].…”
Section: Chemerin In Clinicsmentioning
confidence: 99%
“…Serum concentrations of chemerin is increased in metabolic syndromes and corresponds well with components of metabolic syndrome phenotypes: obesity, adverse lipid profile, increased blood pressure, diabetes and prediabetes, and hepatic steatosis [1,[7][8][9][10]. It contributes to several diabetes complications: diabetic nephropathy, retinopathy, or coronary artery disease (CAD) [2,[11][12][13][14][15]. It is elevated in patients with dilated cardiomyopathy [16].…”
Section: Chemerin In Clinicsmentioning
confidence: 99%
“…Aside from the cell/layer-specific effects of chemerin on the microvasculature, chemerin promotes angiogenesis, which is more elevated in type 2 diabetes mellitus patients with microvasculature complications. 50 , 51 Chemerin’s positive association with angiogenesis is typically viewed through the lens of carcinogenesis, an area with a greater literature. 52 …”
Section: Chemerin’s Mechanistic Influence Over Blood Pressure and Hypmentioning
confidence: 99%
“… 40 , 41 Among the genes downregulated in DR, AHI1 encodes a cilia-localized protein, and its absence promotes retinal degeneration. 42 CMKLR1 is activated by the Wnt/β-catenin pathway, which is involved in extracellular matrix accumulation and renal fibrosis in DR. 43 , 44 However, the pathogenic role of CMKLR1 in retinal microvascular function has not been evaluated in vivo or in vitro. EXOSC7 has been reported to be differentially expressed between T1DM and healthy controls, 45 but no study has been found showing its altered expression in DR. INTS6 is a glucocorticoid response gene, and glucocorticoids have gluconeogenesis promoting effects on the liver.…”
Section: Discussionmentioning
confidence: 99%